Analysis of Household Electricity Consumption Patterns and Economy of Water Heating Shifting and Saving Bulbs - Rosin, Argo; Moller, Taavi; Lehtla, Madis; Hoimoja, Hardi (Electrical, Control and Communication Engineering, 2010)
This article analyses household electricity consumption based on an object in Estonia. Energy consumption of workday and holiday by loads (including high and low tariff energy consumption) is discussed. The final part describes the evaluation of profitability of common investments of consumption shifting and replacing inefficient devices with more efficient ones. Additionally it describes shifting problems and shifting equipment profitability in real-time tariff system.